Understanding the influence of physical resources and social supports on primary food providers' snack food provision: a discrete choice experiment - Brittany J. Johnson; Rebecca K. Golley; Dorota Zarnowiecki; Gilly A. Hendrie; Elisabeth K. Huynh (BMC, 2020)
Abstract Background Snack eating occasions contribute approximately a third of children's energy intake, with approximately half of all unhealthy foods consumed during snack times. Therefore, it is critical to understand the drivers of primary food providers' snack provision. The study aims were to determine the relative importance of physical resources and social supports when primary food providers are choosing snacks to provide to their child, and to investigate how these attributes differ in social versus non-social occasions, and between subgroups of primary food providers based on socio-economic position. Methods Primary food providers of three to seven-year olds completed an online discrete choice experiment, by making trade-offs when completing repeated, hypothetical choice tasks on the choice of snacks to provide to their child in: 1) non-social and 2) social condition. Choice tasks included two alternatives consisting of varying attribute (i.e. factor) levels, and an opt-out option. The order of conditions shown were randomized across participants. Multinomial logit model analyses were used to determine utility weights for each attribute. Results Two-hundred and twenty-five primary food providers completed the study, providing 1125 choice decisions per condition. In the non-social condition, the top three ranked attributes were type of food (utility weight 1.94, p < 0.001), child resistance (− 1.62, p < 0.001) and co-parent support (0.99, p < 0.001). In the social condition, top ranking attributes were child resistance (utility weight − 1.50, p < 0.001), type of food (1.38, p < 0.001) and co-parent support (1.07, p < 0.001). In both conditions, time was not a significant influence and cost was of lowest relative importance. Subgroup analyses revealed cost was not a significant influence for families from higher socio-economic backgrounds. Conclusions Type of food, child resistance and co-parent support were of greatest relative importance in primary food providers' snack provision decision-making, regardless of social condition or socio-economic position. In designing future interventions to reduce unhealthy snacks, researchers should prioritize these influences, to better support primary food providers in changing their physical and social opportunity. Trial registration Australian New Zealand Clinical Trials Registry no. ACTR N12618001173280